Excessive daytime sleepiness. When to think of narcolepsy? - Rosinha, Inês (2023)
Narcolepsy is a rare entity that has excessive daytime sleepiness (EDS) as chief complaint. It is a lifelong neurological condition that can be dramatically disabling in the life of a child or adolescent. The classic symptomatic tetrad of EDS − cataplexy, hypnagogic hallucinations, and sleep paralysis − is relatively rare and usually not present in early stages of the disorder, making the diagnosis quite challenging. The authors describe two clinical cases of adolescents presenting with EDS in which complementary studies culminated in the diagnosis of narcolepsy. Both cases highlight the importance of a high level of suspicion when dealing with EDS since early diagnosis and treatment of narcolepsy are crucial to improve patients’ quality of life and minimize the negative impact on school performance and social repercussions.